2022
DOI: 10.21037/tp-21-557
|View full text |Cite
|
Sign up to set email alerts
|

Surgical options for proximal and distal transverse arch hypoplasia in infants with coarctation

Abstract: Background: Although various surgical techniques have been reported for aortic arch reconstruction for proximal and distal transverse arch (PDTA) hypoplasia, no consensus has been reached on a surgical option for initial arch reconstruction. This study was undertaken to review various arch reconstruction options for PDTA hypoplasia in Chinese infants. Methods: A retrospective review of 121 infants who underwent initial arch reconstruction of the proximal and distal aortic arches between 2010 and 2020 was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The use of a patch can sufficiently expand the hypoplastic segment to prevent recoarctation and achieve a relatively normal geometry [18,20]. In a study comparing ESA and patch aortoplasty techniques, a lower incidence of recoarctation was reported in the patch group [21]. Li et al [21] reported that the ESA method was preferable to patch aortoplasty in patients for whom ESA was suitable (i.e., individuals in which descending aorta mobilization was not limited and aortic arch geometry was normal).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a patch can sufficiently expand the hypoplastic segment to prevent recoarctation and achieve a relatively normal geometry [18,20]. In a study comparing ESA and patch aortoplasty techniques, a lower incidence of recoarctation was reported in the patch group [21]. Li et al [21] reported that the ESA method was preferable to patch aortoplasty in patients for whom ESA was suitable (i.e., individuals in which descending aorta mobilization was not limited and aortic arch geometry was normal).…”
Section: Discussionmentioning
confidence: 99%
“…In a study comparing ESA and patch aortoplasty techniques, a lower incidence of recoarctation was reported in the patch group [21]. Li et al [21] reported that the ESA method was preferable to patch aortoplasty in patients for whom ESA was suitable (i.e., individuals in which descending aorta mobilization was not limited and aortic arch geometry was normal). The authors noted that the ESA method was associated with fewer procedures and a shorter ASCP time.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, significant progress has been made in studying factors influencing the short-term and long-term outcomes of patients with coarctation of the aorta. The anatomical structure of the patient's aorta, nutritional status, surgical methods, and surgical approaches influence surgical prognosis ( 9 11 ). This study further identified risk factors associated with prolonged ICU stay in infants with simple CoA.…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, an incision was made along the inferior aspect of the aortic arch, usually between the innominate artery and descending aorta, and when posterior anastomosis was completed, the remaining anterior aspect of the aortic arch was supplemented with the autologous main pulmonary artery patch harvested. 6,16,17 A surgical alternative was available for patients who had a long isthmic portion (subtype b) and a sizable transverse aortic arch regardless of the anatomical features of the aortic arch. Recently, we performed modified end-to-end anastomosis combined with subclavian artery flap aortoplasty in two patients with pre-operative airway compression, as previously described.…”
Section: Surgical Approach and Techniquesmentioning
confidence: 99%
“…The optimal surgical treatment for coarctation of the aorta remains controversial, in particular, in patients with tubular hypoplasia of the aortic arch. Therefore, diverse surgical techniques, including end-to-end anastomosis, subclavian artery flap aortoplasty, extended end-to-end anastomosis, 1,2 end-to-side anastomosis, 3,4 patch 5,6 or conduit repair, and other alternative options, 7 with or without cardiopulmonary bypass, have been used. We believe that the management of coarctation of the aorta should be based on the anatomical and morphological features of the aortic arch and isthmic portion.…”
mentioning
confidence: 99%